Introduction to spectroscopy / Donald L. Pavia, Gary M. Lampman, George S. Kriz, James R. Vyvyan - Pavia, Donald L.; Lampman, Gary M.; Kriz, George S.; Vyvyan, James R. (Cengage Learning, 2015)
Gain an understanding of the latest advances in spectroscopy with INTRODUCTION TO SPECTROSCOPY.This proven book provides a systematic introduction to spectra and basic theoretical concepts in spectroscopic methods and includes up-to-date spectra; a modern presentation of one-dimensional nuclear magnetic resonance (NMR) spectroscopy; an introduction to biological molecules in mass spectrometry; and coverage of modern techniques alongside DEPT, COSY, and HECTOR.